Dataset of the lab-scale 3-axis winding machine integrated with the portable real-time winding angle measurement system - Quanjin, Ma; Mohd Ruzaimi, Mat Rejab; Muhammad Syafiq, Idris (Elsevier Inc., 2022)
This article presents three datasets related to the laboratory scale 3-axis filament winding machine. The winding experimental tests are described on the range of winding angle, winding accuracy of programmed G-codes, and linear and rotation speeds in raw data. The real-time winding angle measurement system is developed to monitor and measure the winding angle of filament-wound carbon-fiber reinforced plastics (CFRP) tubes. Two winding patterns are provided as dry and wet winding processes. Moreover, an experimental test of a real-time winding angle measurement system is captured and analyzed. The i-winder app controls the winding machine through a Bluetooth module, which is programmed by MIT App Inventor. The data presented in this article can have a benchmark for developing a multi-axis filament winding machine. It is provided an inexpensive and open-source control system and is embedded in a real-time winding angle measurement system. The experimental assessment data can be found in this article [1]. The data is available in the cloud-based Mendeley Data repository [2].